Comparison of HPV testing and cervical cytology in prevention of cervical cancer - Remjasz, Klaudia; Kosz, Katarzyna; Kuchnicka, Aleksandra; Kuchnicka, Julia; Aleksandrowicz, Jakub; Zielińska, Martyna; Zarankiewicz, Natalia; Siedlecki, Wojciech; Sapuła, Klaudia (Journal of Education, Health and Sport, 2022)
Introduction and purpose This article aims to compare two guiding methods of cervical cancer screening: cervical cytology and HPV testing. The objective is to provide information on which method is currently more relevant in the early detection of precancerous lesions and and therefore should be more frequently used. Materials and method This review was mainly based on articles from around the world collected in Pubmed in 2003-2022, medical books and websites. The research was done by looking through keywords as follows: “cervical cancer”, “cytology”, “HPV testing”. Results All selected studies have demonstrated that HPV testing is a more appropriate indicator for initial high-grade CIN (cervical intraepithelial neoplasia) than cytology. Conclusions According to the cited researches, the public health system should definitely pay more attention to HPV testing as the first stage of cervical cancer screening. Moreover, it should clarify by comparing all advantages and disadvantages of methods, which further diagnostic pathway is the most effective and has the best outcomes for the patients. Keywords cervical cancer, cervical screening, cytology, HPV primary screening, HPV testing